Users’ and therapists’ perceptions of myoelectric multi-function upper limb prostheses with conventional and pattern recognition control - Franzke, Andreas W.; Kristoffersen, Morten B.; Bongers, Raoul M.; Murgia, Alessio; Pobatschnig, Barbara; Unglaube, Fabian; van der Sluis, Corry K. (PloS one, 2019)
To describe users' and therapists' opinions on multi-function myoelectric upper limb prostheses with conventional control and pattern recognition control. Qualitative interview study. Two rehabilitation institutions in the Netherlands and one in Austria. The study cohort consisted of 15 prosthesis users (13 males, mean age: 43.7 years, average experience with multi-function prosthesis: 3.15 years) and seven therapists (one male, mean age: 44.1 years, average experience with multi-function prostheses: 6.6 years). Four of these users and one therapist had experience with pattern recognition control. This study consisted of semi-structured interviews. The participants were interviewed at their rehabilitation centres or at home by telephone. The thematic framework approach was used for analysis. The themes emerging from prosthesis users and therapists were largely congruent and resulted in one thematic framework with three main themes: control, prosthesis, and activities. The participants mostly addressed (dis-) satisfaction with the control type and the prosthesis itself and described the way they used their prostheses in daily tasks. Prosthesis users and therapists described multi-function upper limb prostheses as more functional devices than conventional one-degree-of-freedom prostheses. Nonetheless, the prostheses were seldom used to actively grasp and manipulate objects. Moreover, the participants clearly expressed their dissatisfaction with the mechanical robustness of the devices and with the process of switching prosthesis function under conventional control. Pattern recognition was appreciated as an intuitive control that facilitated fast switching between prosthesis functions, but was reported to be too unreliable for daily use and require extensive training.